2021
DOI: 10.1097/tme.0000000000000371
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Age on Propofol Dosing Requirements During Procedural Sedation in the Emergency Department

Abstract: Propofol is a frequently used agent for procedural sedation in the emergency department (ED). Some have suggested that propofol dosing in this setting should be adjusted in elderly patients; however, limited data exist supporting this recommendation. Additional factors that may contribute to altered propofol dose requirements in this setting have not been thoroughly explored. The objective of this analysis was to ascertain the effect age may have on the propofol dose required during procedural sedation in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(38 reference statements)
0
0
0
Order By: Relevance
“…Shafer et al reported that the pharmacokinetics of propofol included a total body clearance rate of 2.09 ± 0.65 L/min and an elimination half-life of 116 ± 34 min 9 . Studies have consistently shown that clearance rates of propofol in elderly patients are significantly lower than in younger patients, indicating that age is a significant factor affecting propofol metabolism 10 , 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Shafer et al reported that the pharmacokinetics of propofol included a total body clearance rate of 2.09 ± 0.65 L/min and an elimination half-life of 116 ± 34 min 9 . Studies have consistently shown that clearance rates of propofol in elderly patients are significantly lower than in younger patients, indicating that age is a significant factor affecting propofol metabolism 10 , 11 .…”
Section: Discussionmentioning
confidence: 99%